PERILAKU PICKY EATER DAN STATUS GIZI PADA ANAK USIA PRASEKOLAH - Novika, Revi Gama Hatta; Jalilah, Nurul Hidayatun; Irawan, Irlina Raswanti; Indriani, Ririn; Sendra, Eny (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Picky eaters are children's habits to be picky about certain types of food and refuse food. The initial survey which was conducted in 3 Kindergartens in the City of Bagansiapiapi, found that there were 7 preschool children who experienced picky eaters. The research objective was to determine the picky eater behavior and nutritional status of preschool children at the Kindergarten Trisula Kota Bagansiapiapi in 2020. The study was a quantitative, analytic observational study with a case control design which was carried out in Trisula Kindergarten in March-April 2020 with 23 case samples and control samples. 23 people. Univariate and bivariate data analysis used the Chi Square Test. The results showed that there was no relationship between picky eating behavior and nutritional status (p value = 1,000, POR = 0.758) as well as maternal knowledge (p value = 0.007, OR = 6.750), parenting style (p value = 0.039, OR = 4.286), breastfeeding. exclusive (p value = 0.037, OR = 4.407) is a risk factor for picky eater behavior. The conclusion of this research shows that picky eater behavior is not related to nutritional status and knowledge of mother, parenting style, exclusive breastfeeding is related to picky eater behavior. It is suggested to Trisula Kindergarten to collaborate with the closest health center, especially the health promotion section, to conduct counseling activities about picky eater behavior.Keywords: Toddler, Education, Knowledge, Integrated Service Post, Attitude